Chinese cabbage orphan gene BR3 confers bolting resistance to Arabidopsis through the gibberellin pathway - Zhang, Yuting; Jiang, Mingliang; Sun, Shurui; Zhan, Zongxiang; Li, Xiaonan; Piao, Zhongyun (Frontiers in Plant Science, 2025)
Premature bolting reduces the yield and quality of Chinese cabbage, making bolting resistance gene identification crucial for breeding superior and stable varieties. In this study, we identified an orphan gene BOLTING RESISTANCE 3 (BR3) that positively regulates bolting resistance in Arabidopsis thaliana. The expression of BR3 was developmentally regulated and occurred during the seedling and flowering stages. The BR3 protein was localized to both the plasma membrane and nucleus. Arabidopsis BR3 overexpressing (BR3OE) plants exhibited delayed bolting and flowering times, an increased number of rosette leaves, reduced plant height, and fewer siliques under long-day (LD) conditions. Key flowering genes were significantly downregulated in BR3OE plants. BR3OE plants similarly exhibited delayed bolting and flowering times, and an increased number of rosette leaves under short-day (SD) conditions. BR3OE plants showed no significant phenotypic differences after vernalization treatment. BR3OE and WT plants exhibited early flowering after GA3 treatment, and bolting and flowering time remained delayed in BR3OE plants compared with WT plants. Key DELLA genes BrRGA1 and BrRGL3 exhibited a co-expression pattern consistent with BR3 gene in Chinese cabbage, which suggested that BrRGA1 and BrRGL3 genes may directly or indirectly regulated by BR3 gene. BR3 gene increased bolting resistance perhaps by upregulating the expression of DELLA genes in the GA pathway. This study provides new theoretical insights for addressing premature bolting in Chinese cabbage and offers novel approaches for breeding bolting-resistant varieties.